Whose victory? A perspective on shifts in US-China cross-border data flow rules in the AI era. - Xu, Wanxiu; Wang, Shuo; Zuo, Xiaodong (Pacific Review, 2025)
The rise of artificial intelligence (AI) is transforming cross-border data governance, a globally significant issue. This study examines the regulatory shifts in cross-border data flows between two superpowers—China and the US—in the AI era. It highlights how the strategic value of data flows has introduced a new dimension of great power competition in technology, supplementing pre-existing concerns such as digital trade, national security, and data privacy protection, while intensifying associated security risks. The US is transitioning from liberal to restrictive regulation, whereas China is gradually shifting from restrictive regulation toward greater openness. These changes reflect both nations' recalibrations based on their respective national interests, emphasizing divergent priorities in technological power contests, evolving trade strategies, and policy objectives amidst a new wave of technological transformation. This article provides a forward-looking analysis of next-generation cross-border data flow regulations in the AI era, addressing gaps in existing research focused on traditional data flow governance. It also offers strategic insights into the regulatory transformations in China and the US, with implications for global data governance.